F-theory uplifts and GUTs - Blumenhagen, Ralph; Weigand, Timo (Arxiv, 2009)
We study the F-theory uplift of Type IIB orientifold models on compact Calabi-Yau threefolds containing divisors which are del Pezzo surfaces. We consider two examples defined via del Pezzo transitions of the quintic. The first model has an orientifold projection leading to two disjoint O7-planes and the second involution acts via an exchange of two del Pezzo surfaces. The two uplifted fourfolds are generically singular with minimal gauge enhancements over a divisor and, respectively, a curve in the non-Fano base. We study possible further degenerations of the elliptic fiber leading to F-theory GUT models based on subgroups of E8.